2021
DOI: 10.1111/jzs.12471
|View full text |Cite
|
Sign up to set email alerts
|

Transalpine dispersal: Italian barred grass snakes in southernmost Bavaria—This far but no further!

Abstract: Based on 1031 samples of grass snakes from Central Europe, we examine the recently reported occurrence of the southern subspecies of the barred grass snake (Natrix helvetica sicula) in southern Bavaria, Germany. Using 13 microsatellite loci and mtDNA coding for the cytb gene and the partial ND4 gene plus adjacent tRNAs, we show that N. h. sicula is restricted to a few river valleys (Inn, Isar, Loisach) in southernmost Bavaria and adjacent Tyrol, Austria. At the widening of the river valleys into the pre‐Alpine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…A total of 181 tissue samples (115 N. natrix, 66 N. tessellata) were newly processed and microsatellite data were generated for 15 additional samples of N. natrix with previously published mtDNA sequences (Kindler et al 2013(Kindler et al , 2017. The remaining data originate from earlier studies (Guicking et al 2006(Guicking et al , 2009Kindler et al 2013Kindler et al , 2017Kyriazi et al 2013;Asztalos et al 2021a). Among our material were five samples of big-headed grass snakes from the putative distribution range of N. megaloce phala that were, according to their morphology, tentatively identified with this nominal species (Table S1).…”
Section: Sampling and Laboratory Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 181 tissue samples (115 N. natrix, 66 N. tessellata) were newly processed and microsatellite data were generated for 15 additional samples of N. natrix with previously published mtDNA sequences (Kindler et al 2013(Kindler et al , 2017. The remaining data originate from earlier studies (Guicking et al 2006(Guicking et al , 2009Kindler et al 2013Kindler et al , 2017Kyriazi et al 2013;Asztalos et al 2021a). Among our material were five samples of big-headed grass snakes from the putative distribution range of N. megaloce phala that were, according to their morphology, tentatively identified with this nominal species (Table S1).…”
Section: Sampling and Laboratory Proceduresmentioning
confidence: 99%
“…Until a few years ago, the three grass snake species were lumped together in one polytypic species, N. natrix sensu lato (Mertens and Wermuth 1960;Kabisch 1999;Kreiner 2007). However, recent studies using mtDNA sequences and microsatellite loci revealed only limited gene flow across narrow geographic contact zones and led to their recognition as three distinct species (Pokrant et al 2016;Kindler et al 2017;Schultze et al 2019Schultze et al , 2020Asztalos et al 2020Asztalos et al , 2021aSpeybroeck et al 2020). Natrix astreptophora occurs in the northern Maghreb region, the Iberian Peninsula and southwestern France (Mertens and Wermuth 1960;Kabisch 1999).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations